Pragmatism, rights, and democracy - Singer, Beth J., 1927- (American philosophy series ;, 1999)
"This volume of essays is based on Singer's earlier works on the theory of human rights, notably her 1993 book, Operative Rights. It contains several chapters in which she criticizes conventional theories, traditional as well as contemporary, and provides further clarification of her own view. In addition, the book includes applications of Singer's theory to a wide range of topics and issues, including multiculturalism, minority rights, conflict resolution, liberalism, communitarianism, and democracy. Among the philosophers whose work is treated at length are Jean-Jacques Rousseau, Thomas Hill Green, John Stuart Mill, John Dewey, George Herbert Mead, Charles Taylor, Alan Gewirth, and Will Kymlicka. As the title of the book (and the title essay) suggests, in her view of the democratic process, Singer is most influenced by Dewey and Mead."--Jacket